2015
DOI: 10.1007/s10964-015-0394-x
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Associations Between Discrimination, Depressive Symptoms, and Prosocial Behaviors in U.S. Latino/a Recent Immigrant Adolescents

Abstract: The links between discrimination and adjustment in U.S. Latino/a immigrant adolescents is an important but understudied phenomenon. We aimed to investigate the longitudinal associations (across 1 year) among discrimination, prosocial behaviors, and depressive symptoms in U.S. Latino immigrant adolescents using two competing models: associations between discrimination and prosocial behaviors via depressive symptoms (mental health strain model), and associations between discrimination and depressive symptoms via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 56 publications
9
112
4
Order By: Relevance
“…Regression analysis was primarily used, but some employed more sophisticated methods, such as latent class analysis and latent profile analysis to create categories of various exposure variables, including discriminatory experience, cultural stressors, and coping styles [22,28,30,31,44,45]. Techniques were employed by some studies to examine potential intermediary pathways between discrimination and mental health, such as through depressive symptoms or anxiety [19,24,43,46], avoidant coping strategies [33,47], trans diagnostic factors [48], general stress [40], stronger belief in an unjust world [49], acculturation-related and social support variables [13,50,51], anger [46], prosocial behavior [33], and perfectionism [52]. Other studies employed mediation techniques to examine if discrimination was on the pathway between a more upstream exposure, such as childhood adversity [53], historical trauma [28], a perpetual foreigner stereotype [37], white composition of one’s environment [29], critical ethnic awareness [50], and nativity [54], and a mental health outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Regression analysis was primarily used, but some employed more sophisticated methods, such as latent class analysis and latent profile analysis to create categories of various exposure variables, including discriminatory experience, cultural stressors, and coping styles [22,28,30,31,44,45]. Techniques were employed by some studies to examine potential intermediary pathways between discrimination and mental health, such as through depressive symptoms or anxiety [19,24,43,46], avoidant coping strategies [33,47], trans diagnostic factors [48], general stress [40], stronger belief in an unjust world [49], acculturation-related and social support variables [13,50,51], anger [46], prosocial behavior [33], and perfectionism [52]. Other studies employed mediation techniques to examine if discrimination was on the pathway between a more upstream exposure, such as childhood adversity [53], historical trauma [28], a perpetual foreigner stereotype [37], white composition of one’s environment [29], critical ethnic awareness [50], and nativity [54], and a mental health outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of literature has documented the mental health effects of discrimination in Latino populations specifically (Finch, Kolody, and Vega 2000; Flores et al 2008; Gee et al 2006; Basáñez et al 2013; Behnke et al 2011; Cano et al 2016; Davis et al 2016; Delgado et al 2011; Roblyer et al 2016). Our results support the findings of these prior studies, which suggest that Latinos in the US may be particularly vulnerable to discrimination’s adverse effects on mental health due to the multiple avenues by which discrimination may enter their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies that have shown that depression is predictive of later erosion in social support among adolescent girls, possibly because depressed individuals tend to engage in behaviors such as constantly seeking reassurance that may lead to peer rejection (Stice, Ragan, & Randall, 2004). Additionally, depressive symptoms may lead to a depletion of cognitive and emotional resources and a subsequent withdrawal from social relationships (Davis et al, 2016). Similarly, behaviors associated with PTSD symptoms, such as aggression, may undermine supportive relationships in school (Kendra, Bell, & Guimond, 2012).…”
Section: Discussionmentioning
confidence: 99%